Metode 划线分析法 [huàxiàn fēnxī fă] untuk meningkatkan kualitas pembelajaran analisis pola kalimat matakuliah sintaksis Bahasa Mandarin - Putri, Amira Eza Febrian; Laksana, Karina Fefi; M, Okti Rjeky; Sunarti, Sunarti (2021)
To improve the quality of online learning during the pandemic, students need an efficient and easy-to-understand method. The 划线分析法 [huàxiàn fēnxī fă] method is a method of analyzing sentence patterns using lines that represent each element of a word in a sentence. The 划线分析法 [huàxiàn fēnxī fă] method is useful for training students' analytical skills while increasing attractiveness because it uses different line patterns and colors to analyze a sentence. The purpose of this study was to find out how to apply the 划线 分析法 [huàxiàn fēnxī fă] method in optimizing the learning of Mandarin sentence analysis in Mandarin syntax courses. The data is collected using zoom recordings and observation records. The results showed the quality of the learning process in the analysis of complex sentences of Mandarin syntax improved. Through the application of these methods, from the observations made, students who previously had difficulty analyzing sentences gained a deep understanding in analyzing sentences.